MgO–ZrO2 Ceramic Composites for Silicomanganese Production - Gómez Rodríguez, Cristian; García Quiñonez, Linda Viviana; Aguilar Martínez, Josué Amilcar; Castillo Rodríguez, Guadalupe Alan; Rodríguez Castellanos, Edén Amaral; López Perales, Jesús Fernando; Mendivil Palma, María Isabel; Verdeja, Luis Felipe; Fernández González, Daniel (Molecular Diversity Preservation International, 2022)
The deterioration of the refractory lining represents a significant problem for the smooth operation in the ferroalloys industry, particularly in the production of silicomanganese, due to the periodic requirements of substitution of the damaged refractory. Within this context, magnesia refractories are commonly employed in the critical zones of the furnaces used in silicomanganese production since the slag involved in the process has a basic character. The behavior of MgO–ZrO2 ceramic composites with different ZrO2 nanoparticles (0, 1, 3, and 5 wt.%) contents in the presence of silicomanganese slags is proposed in this manuscript. XPS, XRD and SEM–EDX were used to evaluate the properties of the ceramic composite against the silicomanganese slag. The static corrosion test was used to evaluate the corrosion of the refractory. Results suggest that corrosion is controlled by the change in slag viscosity due to the reaction between CaZrO3 and the melted slag. Besides, ZrO2 nanoparticles located at both triple points and grain boundaries act as a barrier for the slag advance within the refractory. The utilization of MgO refractories with ZrO2 nanoparticles can extend the life of furnaces used to produce silicomanganese.